Optimum currency area index for the economic community of West African states (ECOWAS) - Ngozi Eunice Egbuna; Ismaila Jarju; Sani Bawa; Ibrahim Diallo; Olukayode S. Odeniran; Isatou Mendy; Edward Nyarko (West African Monetary Institute (WAMI), 2019)
This study assesses the speed of real convergence in ECOWAS using the Optimal Currency Area (OCA) theory to determine the readiness of member countries for a monetary union. The study leveraged on Bayoumi and Eichengreen (1996) and computed OCA indices utilizing both variables suggested by the traditional OCA criteria and the new variables identified in the literature. Empirical results from the analysis showed that ECOWAS countries could be divided into three groups: those exhibiting high level of real convergence and would be ready to join the monetary union at the proposed date of 2020, those exhibiting medium level of convergence and may be ready for the union shortly after 2020, and those converging slowly and would require more time to achieve convergence. Additional results indicated that UEMOA countries have achieved real convergence and the single currency programme benefitted the countries at least in line with the OCA analysis. The results also showed that small countries stand to benefit most from joining a monetary union than having its own currency. The study recommends that the formation of an ECOWAS monetary union should assume a gradual approach. In the interim, however, WAMZ countries should intensify efforts to meet the ECOWAS nominal macroeconomic convergence criteria on a sustained basis, as this would make the countries move faster towards real convergence.
Keywords: C33; C43; F15; O55; 330; Optimum Currency Area; real convergence; Business cycle asymmetry; tradelinkages; ECOWAS